Solid surface composite materials manufactured from syrup of polymethyl methacrylate, alumina trihydrate and natural mineral fillers - Adan A. (2020)
A composite material, which properties are similar to the commercial material Krion®, was manufactured using polymethyl methacrylate (PMMA) syrup, alumina trihydrate (ATH) and natural mineral fillers (CMN). For this purpose, composites have been manufactured in 2 stages: In first stage, free radical polymerization of methyl methacrylate (MMA) was carried out to obtain syrup of polymethyl methacrylate. Polymerization parameters were determined in order to avoid autoacceleration effect and to get syrup which PMMA conversion avoids precipitation of ATH particles. In second stage, composite samples were manufactured using the obtained syrup, ATH and CMN particles and, then, they were tested in order to determine suitable parameters to get similar properties to Krion®. It has been proved that syrup must have a MMA to PMMA conversion between 20% and 25% to avoid autoacceleration effect and precipitation of ATH particles. To obtain such syrup, polymerization must be carried out using 0,1% of benzoyl peroxide (PBO) y 0,2% of ethylene glycol dimercaptoacetate (EGDM) at 85°C during 90 minutes. Similarly, to get composites which properties are similar to Krion®, the manufacturing parameters of a PMMA composite reinforced with ATH and CMN particles are: 40% syrup / 60% ATH / %CMN variable according to the type of filler, 0,1% of additional PBO, 2,0% ethylene glycol dimethacrylate (EGDMA) y curing time 13 hours inside a furnace at 85°C. Properties of the composite that has been manufactured under these conditions and only contains ATH filler are: flexural resistance of 53 MPa, flexural elastic modulus of 8054 MPa and hardness of 91 HRM. Esthetic quality improves with the incorporation of CMN but mechanical properties decrease. © 2020, Universidade Federal do Rio de Janeiro. All rights reserved.